2020
DOI: 10.12944/cwe.15.1.07
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Accidental Injuries among Building Construction Workers in Bangladesh

Abstract: The construction sector is the biggest and most unsafe venture compared to other sectors of the world. The workers in this sector are more prone to accidental injuries. There are different types of agents and lacking for this type of injuries. The objectives of this study were to investigate the prevalence of accidental injuries among building construction workers in Bangladesh. The agents and lacking behind these injuries also investigated. A survey on 390 building construction workers was conducted through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
5
1
Order By: Relevance
“…Several studies have reported an association between occupational injuries and psychological and behavioural factors. 2 6–8 12 21 However, alcohol consumption in this study is deemed a protective factor to occupational injuries among building construction workers (aOR 0.269, 95% CI 0.076 to 0.947), and this finding contradicts many studies conducted in sub-Saharan Africa. 2 6–8 12 21 Few respondents reported that they consumed alcohol, and all of them consumed it after work and off day.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Several studies have reported an association between occupational injuries and psychological and behavioural factors. 2 6–8 12 21 However, alcohol consumption in this study is deemed a protective factor to occupational injuries among building construction workers (aOR 0.269, 95% CI 0.076 to 0.947), and this finding contradicts many studies conducted in sub-Saharan Africa. 2 6–8 12 21 Few respondents reported that they consumed alcohol, and all of them consumed it after work and off day.…”
Section: Discussioncontrasting
confidence: 94%
“…[5][6][7][8] Although hazards exist in all occupations with the potential to cause injury to workers, the construction industry work environment is responsible for most occupational injuries. 2 It has been reported to be the second-largest cause of occupational injuries, causing public health and socioeconomic problems. 9 Globally, occupational fatalities claim up to 20% of the global mortality burden out of every 5000 deaths; thus, 1 in every 5 is occupationally related.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Similarly, in Bangladesh, about 63.80% of the construction workers suffered from workplace injuries, out of which, 24.7% were attributed mainly to falls from heights and poor safety facilities. 6 Hong Kong recorded 76% of fatal accidents in the construction industry in 2017. 7 Limited compliance with the safety culture at the workplace was the possible cause aside from various causes of non-fatal accidents.…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of construction workers tends to increase in line with its expansion because it is still primarily reliant on human labor (Sourav, 2019). According to the Bangladesh Construction Workers Union and the Real Estate & Housing Association of Bangladesh (REHAB), the construction industry employs approximately 3.5 million people (Rahman et al, 2020). Bangladesh has 4000 construction firms, according to the Bangladesh Association of Construction Industry (BACI), with 100 of them capable of completing projects in other countries (Ahmed, 2014).…”
Section: Introductionmentioning
confidence: 99%